RETRACTED: A Novel Tumor Suppressor Gene, ZNF24, Inhibits the Development of NSCLC by Inhibiting the WNT Signaling Pathway to Induce Cell Senescence - Pang, Bo; Wang, Yong; Chang, Xiaoyan (Frontiers in Oncology, 2021)
Abstract Object Understanding the characteristics of tumor suppressor genes (TSGs) is of great significance for the development of new targeted treatment strategies for non-small cell lung cancer (NSCLC). Therefore, this present article is to explore the underlying molecular mechanism of ZFN24 inhibiting the development of NSCLC. Methods We performed RT-PCR and Western Blotting for evaluating associated RNA and protein expression. CCK8, colony forming and sphere-forming assays were used to evaluate the proliferation and stemness of NSCLC cells. NSCLC cells senescence were examined by β-galactosidase staining assay. Luciferase assay was performed to evaluate β-catenin transcriptional activity. The effect of ZNF24 on NSCLC cells in vivo was evaluated by the xenograft tumor experiment. Results Ectopic expression of ZNF24 significantly inhibited cell viability, colony forming ability and stemness of NSCLC cells. Wnt signaling pathway was inhibited by ZNF24 resulted in NSCLC cells senescence. And β-catenin transcriptional activity was significantly inhibited by ZNF24 (P<0.05). Ectopic expression of ZNF24 significantly inhibited xenotransplant tumors growth in vivo (P<0.05). Conclusion ZNF24 could notably inhibited the development of NSCLC by inhibiting the Wnt signaling pathway.